Доблестите и комерцијалното општество: Адам Смит и phronesis - Поповска, Јасмина (Филозофско друштво на Македонија, 2024)
The name “Das Adam Smith Problem” refers to the discussion held by German scholars in the second half of the 19th century regarding whether Adam Smith’s views on self-interest expressed in The Wealth of Nations (1776) could be reconciled with those on human nature and the role of empathy in our ethical action set forth in The Theory of Moral Sentiments (1759). Leaving aside the scholarly debate on whether this problem is still theoretically relevant, the impression remains that it reflects the classic question of the possibility of postulating self-interest as an organizing principle of economic activity within a broader and consistent moral framework. This text will address this classic question through phronesis as a concept that may prove to be crucial for understanding Smith’s ideas. Phronesis as an intellectual virtue, ever since its explicit definition by Aristotle, carries the potential for reconciling many oppositions that arise from ethical decision making and action. The two key oppositions in Smith’s philosophy—that is, the opposition between the self and the other and between the moral and the economic—will thus be examined in this text through phronesis.